2001
DOI: 10.1074/jbc.m008330200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Transcription Factor STAT-1α in Insulinoma Cells Protects against Cytotoxic Effects of Multiple Cytokines

Abstract: Destruction of pancreatic islet ␤-cells in type 1 diabetes appears to result from direct contact with infiltrating T-cells and macrophages and exposure to inflammatory cytokines such as interferon (IFN)-␥, interleukin (IL)-Type 1 diabetes is caused by autoimmune destruction of pancreatic islet ␤-cells. Destruction of ␤-cells appears to result from direct contact with infiltrating T-cells and macrophages and exposure to inflammatory cytokines such as IFN-␥, 1 IL-1␤, and TNF-␣ that such cells produce (1-5). Insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
3
21
2
1
Order By: Relevance
“…We showed that inhibitors of HDAC activity sensitize cells to IFN␥-induced apoptosis, demonstrating that STAT1-dependent signaling protects cells from IFN␥-induced apoptosis. This is consistent with reports that STAT1 can protect against cytotoxic effects of multiple cytokines, including IFN␥ and IFN␣ (78,79). Enhanced apoptosis of cells treated with IFN␥ and butyrate suggests that IFN␥ in the absence of STAT1 signaling induces the expression of genes that promote apoptosis or inhibits the expression of antiapoptotic genes.…”
Section: Discussionsupporting
confidence: 79%
“…We showed that inhibitors of HDAC activity sensitize cells to IFN␥-induced apoptosis, demonstrating that STAT1-dependent signaling protects cells from IFN␥-induced apoptosis. This is consistent with reports that STAT1 can protect against cytotoxic effects of multiple cytokines, including IFN␥ and IFN␣ (78,79). Enhanced apoptosis of cells treated with IFN␥ and butyrate suggests that IFN␥ in the absence of STAT1 signaling induces the expression of genes that promote apoptosis or inhibits the expression of antiapoptotic genes.…”
Section: Discussionsupporting
confidence: 79%
“…However, STAT-1a expression was dramatically increased in response to the selection procedure. 25 That the increase in STAT-1a levels might be relevant to the IFN-g resistance induced by the selection procedure was supported by the finding that the increase in expression was observed only in cells that were grown in the continual presence of cytokines, and not in cells subjected to the selection procedure and grown in the absence of cytokines. Recall that cells grown under the latter conditions lose their IFN-g resistance.…”
Section: Development Of Methods For Protecting Insulinoma Cell Lines supporting
confidence: 48%
“…We concluded that induction of STAT-1a makes an important contribution to the IFN-g resistance conferred by our selection procedure. 25 Combined effects of an antiapoptotic gene and cytokine selection…”
Section: Development Of Methods For Protecting Insulinoma Cell Lines mentioning
confidence: 99%
“…Resistance was found to be associated with increased expression of STAT1␣ and could be reproduced by overexpression of STAT1␣ in nonresistant cells, although the biochemical mechanism remains unclear (30). The continual expression of STAT1 in response to IFN-␥ appears to be at odds with the idea of transient IFN-␥-receptor signaling.…”
mentioning
confidence: 69%